E-095 Pre hospital stroke notification and prospective 90-day functional outcome in community hospital. (23rd July 2017) - Klein, B; Adler, N; Shaw, R; Bush, L; Marshall, R; Altschul, D
Abstract : Background: The benefits of pre-hospital stroke notification have been established in numerous studies. Our study prospectively evaluated whether pre-hospital stroke notification is a predictor for improved long-term quality of life and functional independence for patients in a community hospital setting. Methods: Patients >=18 years of age admitted to Valley Community Hospital through the Emergency Department (ED) from April 2015 to May 2016 and were diagnosed with transient ischemic attack and ischemic stroke were included for the the purpose of this analysis. The primary outcomes were length of stay (LOS), modified Rankin Scale (mRS) at discharge and at 90 days, and Quality of Life Global Health score (GHS), along with derived physical and mental health scores, and EQ5D at 90 days determined via phone interview. Comparisons of the primary outcomes were made between patients who arrived by ambulance with pre-hospital stroke notification versus those without prenotification. We also examined for differences between baseline patient characteristics, National Institutes of Health Stroke Scale (NIHSS), and intravenous (IV) tissue plasminogen activator (tPA) administration. All analyses were done using linear and logistic multivariate regression models adjusted for IV tpa administration, gender, age, coronary artery disease, pre hospital notification, means of arrival to the hospital, and time of arrival ( < 8 hours or later). Results: A total of 148 patients were included, and 33 patients had stroke prenotification. At 90 days, we collected data from 114 patients, and 84 of these patients were able to complete the quality of life questionnaire. A higher percentage of patients with stroke prenotification had tPA administration (39.4% vs. 13.9%, p =0.002). In the multivariate analyses, patient who did not get IV tpa were more likely to have a poor mRS 3-6 at 90 days (OR 6.22, p=0.027), and those with severe NIHSS were six times more likely to have a poor mRS of 3-6 at 90 days (OR 6.6, p=0.044). Patients with prehospital notification did not have significant difference in the GHS physical score, mental score, or EQ5D score at 90 days. Results did not change when repeating our analyses with exclusion of walk-in patients to the ED, and the 11 patients who died during study. Conclusion: In a prospective community sample those who received IVtpa and those with milder NIHSS had significantly better 90 day mRS outcomes. Pre hospital stroke notification in itself did not result in better functional or quality of life outcomes at 90 days in this community setting. Disclosures: B. Klein: None. N. Adler: None. R. Shaw: None. L. Bush: None. R. Marshall: None. D. Altschul: None.